DATA WAREHOUSE PENJUALAN PT XYZ - Minda Mora Purba (Fakultas Ilmu Komputer dan Desain - Unsurya, 2018)
AbstractData warehouse is a decision support system (decision support system) which use and manufacture independent in one part of certain business environment at company, for example sales department. Problems faced by this sales is the difficulty in data collection products and customers, and the acquisition of sales reports are fast and accurate. With these problems the company needs a data warehouse that can be a trusted data source for the activities of this company.The process of developing the data warehouse includes the analysis phase, the design stage and implementation.Â Keywords: warehouse, data, DSS, ETL